IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS BLOG DALAM MENINGKATKAN HABITS OF MIND - CASRIATI CASRIATI; SYUKERI GAZALI (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2022)
This Study aims to determine the Implementation of Blog-Based Learning Media in Improving Habits of Mind. The results show that blogging media has a positive effect on students’habits of mind, indicated by an increase in more critical attitude changes. As one of the learning media, blogs provide an avenue for interaction, bth between students and with their teachers outside the classroom. Human intelelligence is seen from the knowledge it has, especially from the way how an individual acts. Having good habits of mind means having the character to behave intelligently when faced with problems of answers that are not immediately known. Habits of mind as a characteristic of intelligent thinking behavior that is the highest in solving problems and is an indicator of success in academics, work and social relationships. The use of blog in improving habits of mind can be seen from three categories, self regulation thinking, critical thinking and creative thinking.